2021
DOI: 10.5897/jene2020.0871
|View full text |Cite
|
Sign up to set email alerts
|

Ecological status of a newly impounded sub-saharan reservoir based on benthic macroinvertebrates community (Burkina Faso, West Africa)

Abstract: In West Africa, particularly in Burkina Faso, the aquatic ecosystems are under human pressures. Therefore, for long term management of these ecosystems, the managers need baseline data for regular assessment of ecological health condition. In this regard, the structure of the benthic macroinvertebrate community was investigated and the relationship between the environmental variables and biotic indices of the Samandéni reservoir from January to December 2018, after one-year impoundment was explored. The macroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Insects constitute the most abundant and divers groups in all sites. These results lie in the same line to those of [4], [6], [7], [8], [9], [10], [18] and [20] who have demonstrated that insects are the most abundant and diverse group in tropical aquatic ecosystems. This can be explained by the fact that insects are resistant groups, and can adapt to different habitat conditions, even those of man-made, as demonstrated by authors [4].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Insects constitute the most abundant and divers groups in all sites. These results lie in the same line to those of [4], [6], [7], [8], [9], [10], [18] and [20] who have demonstrated that insects are the most abundant and diverse group in tropical aquatic ecosystems. This can be explained by the fact that insects are resistant groups, and can adapt to different habitat conditions, even those of man-made, as demonstrated by authors [4].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, these artificial waterbodies are also populated by several species of fish, amphibians and aquatic birds. Many studies have shown that aquatic biota, and particularly the macroinvertebrates are key animals in water because they are mostly influenced by several factors such as ecosystem types, waters variables and multiple anthropogenic pressures [4], [6], [7], [8], [9], [10] and [11]. These men-made lakes provide several advantages but they rarely documented.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in Burkina Faso, the diversity of macroinvertebrate and their relationship with environmental parameters have been undertaken (Guenda, 1996;Kabré et al, 2000;2002;Sanogo et al, 2014;2021;Kaboré et al, 2016a;b;Bancé et al, 2021a;b). But, the shift of macroinvertebrates communities for optimal physico-chemical factors condition is still very poorly documented.…”
Section: Introductionmentioning
confidence: 99%